Overexpression of NtPR-Q Up-Regulates Multiple Defense-Related Genes in Nicotiana tabacum and Enhances Plant Resistance to Ralstonia solanacearum - Tang, Yuanman; Liu, Qiuping; Liu, Ying; Zhang, Linli; Ding, Wei (Frontiers in Plant Science, 2017)
Various classes of plant pathogenesis-related (PR) proteins have been identified in the past several decades. PR-Q, a member of the PR3 family encoding chitinases, has played an important role in regulating plant resistance and preventing pathogen infection. In this paper, we functionally characterized NtPR-Q in tobacco plants and found that the overexpression of NtPR-Q in tobacco Yunyan87 resulted in higher resistance to R. solanacearum inoculation. Surprisingly, overexpression of NtPR-Q led to the activation of many defense-related genes, such as SA-responsive genes NtPR1a/c, NtPR2 and NtCHN50, JA-responsive gene NtPR1b and ET production-associated genes NtACC Oxidase and NtEFE26. Consistent with the role of NtPR-Q in multiple stress responses, NtPR-Q transcripts were induced by the exogenous hormones salicylic acid, ethylene and methyl jasmonate, which could enhance the resistance of tobacco to R. solanacearum. Collectively, our results suggested that NtPR-Q overexpression led to the up-regulation of defense-related genes and enhanced plant resistance to R. solanacearum infection.